The Fifth International Conference of New or Restored Democracies (Ulaanbaatar, Mongolia, 10-12 September, 2003): Ulaanbaatar Declaration (Mongolian Journal of International Affairs, 2013)
DOI: http://dx.doi.org/10.5564/mjia.v0i12.101 Mongolian Journal of International Affairs No.12 2005: 112-120